2014
DOI: 10.1586/14737175.2014.884926
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in understanding the mechanisms of symptomatic lacunar ischemic stroke: translation of knowledge to prevention strategies

Abstract: Symptomatic lacunar ischemic stroke (25% of all brain infarctions) results from occlusion of a single penetrating artery by microatheromas or lipohyalinosis and rarely from an intracranial atheromatous branch disease. Recurrent lacunar stroke may be associated with more severe clinical features and has been involved in producing lacunar state and vascular subcortical dementia. In the first multicenter randomized clinical trial (SPS3) focused on stroke prevention among patients with recent lacunar stroke, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 143 publications
4
46
0
3
Order By: Relevance
“…Our study has some limitations. Although diabetic patients had poorer short-term functional prognosis in our population, previous studies showed that the subgroup of diabetic patients with lacunar infarction shows a better outcome [21,22] . However, magnetic resonance imaging is not available in our institution and imaging of the intra-or extracranial arteries was also not performed in all patients.…”
Section: Discussionmentioning
confidence: 52%
“…Our study has some limitations. Although diabetic patients had poorer short-term functional prognosis in our population, previous studies showed that the subgroup of diabetic patients with lacunar infarction shows a better outcome [21,22] . However, magnetic resonance imaging is not available in our institution and imaging of the intra-or extracranial arteries was also not performed in all patients.…”
Section: Discussionmentioning
confidence: 52%
“…In contrast, studies based on neuroimaging have been definitely more numerous. In a majority of them, BAD-related infarctions were broadly identified as those occurring in the subcortical regions whose blood perfusion depends on deep small penetrating vessels [5,21] . In the anterior circulation, these pertain to lenticulostriate artery terminations stemming from the middle cerebral artery (MCA) and Heubner's artery originating from the anterior cerebral artery [22] .…”
Section: Neuroimaging Featuresmentioning
confidence: 99%
“…Furthermore, current studies clearly show that neuropsychological dysfunction in the initial phase relates more to silent lacunar infarction than to leukoaraiosis or periventricular white matter hyperintensities [22] . This contrasts with the fact that in more advanced stages of the disease, leukoaraiosis will have the greatest importance and greater weight in cognitive impairment of vascular type in patients with cerebral small vessel disease [19,20] . Recurrent lacunar infarction can also cause cognitive impairment.…”
Section: Lacunesmentioning
confidence: 91%
“…The silent lesions tend to be due to a cerebrovascular lipohyalinosis in the perforating arterioles or arteriolar endothelial dysfunction [18] . We must bear in mind that in patients with a first-ever lacunar infarct, 40% of them shows "lacunes" that are clinically silent [19] .…”
Section: Lacunesmentioning
confidence: 99%